Sosialisasi Manajemen Usaha dan Strategi Pemasaran pada UMKM di Desa Melati II - Revita Sari; Randy Harmedia (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Melati II Village, Perbaungan District, there are MSMEs that are objects of community service, namely MSMEs for making tempeh and cultivating maggot caterpillars. The purpose of this community service is (1) to educate on strengthening business management for Tempe MSMEs in Melati II Village, (2) to educate marketing strategies for Maggot Caterpillar MSMEs in Melati II Village. With the increasing understanding of MSME players about the importance of business management and marketing strategies, it is hoped that it will help their businesses to develop and compete better.